Clusters as a Part of Improvement Function of Serbian Economy Real Sector Competitiveness - Svetlana Vukotić; Jugoslav Aničić; Marko Laketa (Amfiteatru Economic Journal, 2013)
One of the reasons for the lack of small and medium enterprises' competitiveness and for large regional disproportions in Serbia is the underdeveloped system of business connectivity that includes clusters, business incubators and technology parks. Setting competitiveness in the centre of the development strategy requires of all businesses subjects new approach development which will allow a better use of existing resources and result in increased export performances. Supporting association into clusters and using their benefits according to the model of highly developed countries is the basis of successful management of economic policy, and all the necessary prerequisites exist in Serbia.
Keywords: L22; L14; 330; clusters; competitiveness; real sector; small and medium enterprises